Electrophysiologic Study of a Method of Euthanasia Using Intrathecal Lidocaine Hydrochloride Administered during Intravenous Anesthesia in Horses. (30th August 2015) - Aleman, M.; Davis, E.; Williams, D.C.; Madigan, J.E.; Smith, F.; Guedes, A.
Abstract : Background: An intravenous (IV) overdose of pentobarbital sodium is the most commonly used method of euthanasia in veterinary medicine. However, this compound is not available in many countries or rural areas resulting in usage of alternative methods such as intrathecal lidocaine administration after IV anesthesia. Its safety and efficacy as a method of euthanasia have not been investigated in the horse. Hypothesis/Objectives: To investigate changes in mean arterial blood pressure and electrical activity of the cerebral cortex, brainstem, and heart during intrathecal administration of lidocaine. Our hypothesis was that intrathecal lidocaine affects the cerebral cortex and brainstem before affecting cardiovascular function. Animals: Eleven horses requiring euthanasia for medical reasons. Methods: Prospective observational study. Horses were anesthetized with xylazine, midazolam, and ketamine; and instrumented for recording of electroencephalogram (EEG), electrooculogram (EOG), brainstem auditory evoked response (BAER), and electrocardiogram (ECG). Physical and neurological (brainstem reflexes) variables were monitored. Mean arterial blood pressure was recorded throughout the study. Results: Loss of cerebro‐cortical electrical activity occurred up to 226 seconds after the end of the infusion of lidocaine solution. Cessation of brainstem function as evidenced by a lack of brainstem reflexes and disappearance of BAER occurred subsequently. Undetectable heart sounds, nonpalpable arterial pulse, and extremely low mean arterial blood pressure supported cardiac death; a recordable ECG was the last variable to disappear after the infusion (300–1, 279 seconds). Conclusions and Clinical Importance: Intrathecal administration of lidocaine is an effective alternative method of euthanasia in anesthetized horses, during which brain death occurs before cardiac death.